Formation of the system of export financing and insurance of export credits in Germany - E. A. Barinov (Путеводитель предпринимателя, 2020)
The article deals with the structure, function and tasks of the state system of export financing of Germany. The role of national banks in lending to export industries was noted. The activities of institutions such as «KB» and «AKA», which played an important role in supporting the export companies of Germany, intensified the markets of foreign countries with their products, were analyzed. Considerable attention was paid to the activities of the insurance company Hermes.